A new species of Brevipalpus Donnadieu (Acari: Tenuipalpidae) and key to the Egyptian species - Halawa, Alaa M.; Fawzy, Magdy M. (Zootaxa, 2014)
A new species, Brevipalpus noranae sp. nov. (Acari: Tenuipalpidae) is described and illustrated from females collected on Malus domestica Borkh and Citrus aurantium L. A key to the species of the genus Brevipalpus present in Egypt is provided.